Bilateral Trade Performance and Future Trade Potential Between India and China : An Empirical Analysis - Islam, Md Kamrul; Rajab, Mudasir; Hoque, Ariful; Ahmed, Mashud (Arthshastra Indian Journal of Economics & Research, 2025)
Purpose : The study aimed to analyze the trend and pattern of India and China’s bilateral trade relationships and evaluate how much their trade complemented one another. It also attempted to identify the commodities having future trade potential between the two nations. Methodology : The study utilized secondary data covering 30 years, from 1991 to 2020, and employed the trade complementarity index (TCI), the revealed comparative advantage (RCA) index, and the revealed import dependence (RID) Index. Findings : Empirical findings revealed that China’s exports to India predominantly consisted of manufactured goods, notably machinery and transport equipment. In contrast, India’s exports included agricultural and manufactured goods but have shifted over the years to be dominated by intermediate goods. The computation of TCI revealed a moderate degree of trade complementarity between the nations, suggesting the possibility for future trade expansion. The study identified 13 commodity classes with future trade potential between India and China by comparing the RCA and the RID indices, highlighting the need for expanded trade to capitalize on this unrealized opportunity. Practical Implications : The study underscored the importance of strengthening India–China bilateral trade agreements, focusing on diversifying India’s technology-driven exports, easing trade barriers, and encouraging joint ventures. These strategies could help balance trade and support mutual economic growth. Originality/Value : To the best of our knowledge, there is a noticeable gap in the literature regarding the identification of commodities with potential for future trade between India and China. Therefore, our study aims to bridge this gap and add to the limited literature in that direction.